Pelatihan Pendampingan Orangtua terhadap Kecerdasan Anak di Era Modernisasi di Desa Wawatu Kecamatan Moramo Utara Kabupaten Konawe Selatan - Roslan, Suharty; Arsyad, Muhammad; Hos, Jamaluddin; Bahtiar; Supiyah, Ratna; Sarpin; Anggraini, Dewi; Ridwan, Harnina (CV. Literasi Indonesia, 2023)
The child is the next generation of the nation, however, often humans forget that the presence of the child is not always in the position of quratul'ain (eye conditioner) but the child can potentially become aduwwan wa fitnatan (enemies and trials), therefore this is part of the task that needs to be considered by parents as a mandate so that parents should provide the best education. The methods used in this counseling and training activity are lectures and discussions/questions and answers and training. Lectures are used to explain, among other things, the positive impacts and negative impacts of media technology well as ways to maximize the positive impact and avoid the negative impact of gadget users on their children. Then continued with a discussion/question and answer about the problem of educating children in using communication technology. This activity has managed to achieve the expected goal. Counseling participants are ultimately able to understand the positive and negative impacts of media technology, as well as be able to understand how to assist children to grow up as a smart generation who can maximize the use of communication technology. The contribution of this training provides awareness for parents, about the importance of educating, educating children using information technology in the era of modernization.